2021
DOI: 10.1186/s12902-021-00808-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between changes in serum myostatin and adiponectin levels in patients with obesity undergoing a weight loss program

Abstract: Background An effective strategy for weight loss in patients who are overweight or obese is to reduce body fat mass while maintaining skeletal muscle mass. Adiponectin and myostatin are affected through changes in body composition due to weight loss, and examining their dynamics may contribute to strategies for maintaining skeletal muscle mass through weight loss. We aimed to examine the relationships among myostatin, adiponectin, and body composition, depending on the extent of weight loss, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Adiponectin is a protein secreted by adipocytes; blood adiponectin concentration correlates inversely with visceral fat weight. Although changes in leptin and adiponectin levels were observed in this study, they could be secondary effects caused by changes in body weight (27). Analysis of other blood components such as aspartate aminotransferase and alanine aminotransferase is a topic for future research.…”
Section: Discussionmentioning
confidence: 69%
“…Adiponectin is a protein secreted by adipocytes; blood adiponectin concentration correlates inversely with visceral fat weight. Although changes in leptin and adiponectin levels were observed in this study, they could be secondary effects caused by changes in body weight (27). Analysis of other blood components such as aspartate aminotransferase and alanine aminotransferase is a topic for future research.…”
Section: Discussionmentioning
confidence: 69%
“…It has been shown that reducing fat tissue while maintaining muscle mass in the weight-loss process in this group of patients leads to an increase in adiponectin concentration. This means that the assessment of serum adiponectin levels can serve as a predictor of the effects of weight loss in patients struggling with obesity [39]. The relationship between adiponectin concentration in the older population and their general condition, muscle mass, and the risk of mortality in this group of patients was investigated by Walowski et al The results suggest that high levels of adiponectin are associated with lower muscle mass, reduced bone mineral content, and lower levels of fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, exercise and diet seem to positively influence adiponectin levels. The study of Takao (2021), for example, analyzed adiponectin levels in obese people before and after a physical exercise program and dietary guidance. The results showed a mean reduction of 7.5% in body composition and an increase in plasma adiponectin concentrations after the end of the program.…”
Section: Introductionmentioning
confidence: 99%